Anti fuzzy ideal extension of semigroups - S. Kumar Majumder; P. Pal; S. K. Sardar (Journal of Hyperstructures, 2012)
In this paper the concepts of anti fuzzy l-prime ideals, anti fuzzy semiprime ideals and anti fuzzy ideal extensions in asemigroup have been introduced. They are found to satisfy characteristic function criterion and anti level subset criterion. Here some properties of anti fuzzy ideal extension of a semigroup have been investigated in terms of anti fuzzy l-prime and anti fuzzy semiprime ideals. Among other results we obtain characterization of l-prime ideals of a semigroup in terms of anti fuzzy ideal extension.